Retention of mothers and infants in the prevention of mother‐to‐child transmission of HIV programme is associated with individual and facility‐level factors in Rwanda. (20th July 2016) - Woelk, Godfrey B; Ndatimana, Dieudonne; Behan, Sally; Mukaminega, Martha; Nyirabahizi, Epiphanie; Hoffman, Heather J; Mugwaneza, Placidie; Ribakare, Muhayimpundu; Amzel, Anouk; Phelps, B Ryan
Abstract : Objectives: Investigate levels of retention at specified time periods along the prevention of mother‐to‐child transmission (PMTCT) cascade among mother‐infant pairs as well as individual‐ and facility‐level factors associated with retention. Methods: A retrospective cohort of HIV‐positive pregnant women and their infants attending five health centres from November 2010 to February 2012 in the Option B programme in Rwanda was established. Data were collected from several health registers and patient follow‐up files. Additionally, informant interviews were conducted to ascertain health facility characteristics. Generalized estimating equation methods and modelling were utilized to estimate the number of mothers attending each antenatal care visit and assess factors associated with retention. Results: Data from 457 pregnant women and 462 infants were collected at five different health centres (three urban and two rural facilities). Retention at 30 days after registration and retention at 6 weeks, 3, 6, 9 and 12 months post‐delivery were analyzed. Based on an analytical sample of 348, we found that 58% of women and 81% of infants were retained in care within the same health facility at 12 months post‐delivery, respectively. However, for mother‐infant paired mothers, retention at 12 months was 74% and 79% for their infants. Loss to facility occurred early, with 26% to 33% being lost within 30 days post‐registration. In a multivariable model retention was associated with being married, adjusted relative risk (ARR): 1.26, (95% confidence intervals: 1.11, 1.43); antiretroviral therapy eligible, ARR: 1.39, (1.12, 1.73) and CD4 count per 50 mm 3, ARR: 1.02, (1.01, 1.03). Conclusions: These findings demonstrate varying retention levels among mother‐infant pairs along the PMTCT cascade in addition to potential determinants of retention to such programmes. Unmarried, apparently healthy, HIV‐positive pregnant women need additional support for programme retention. With the significantly increased workload resulting from lifelong antiretroviral treatment for all HIV‐positive pregnant women, strategies need to be developed to identify, provide support and trace these women at risk of loss to follow‐up. This study provides further evidence for the need for such a targeted supportive approach.